Les relations transpubliques - André-A. Lafrance (Communication)
It is difficult to situate public relations in the conceptual arborescence of knowledge mobilized in what we would like to consider as communication « science ». One of the solutions to this ambiguity would be to displace the observation from the apparent specificity of public relations to the role played by practitioners subjected to the rebound effect of messages directed to each of their audiences, within the framework of a trans-public approach. The case of a communications officer in a municipality confronted with the demands of elected managers and with the opposing expectations of the different internal and external groups illustrates the difficulty of respecting the proclaimed virtues of transparency, belonging, and coherence.